Mapping the "SNAP Gap" – Identifying Neighborhood-level Hot Spots and Cold Spots of SNAP Under-participation in Texas. Issue 4 (4th July 2022) - Ramphul, Ryan; Sharma, Shreela; Revere, Frances Lee; Highfield, Linda
ABSTRACT: This cross-sectional descriptive study utilized spatial statistics to test for hot/cold spots of SNAP under-participation in Texas. First, we estimated the percentage of SNAP eligible but not enrolled (EBNE) households, by census tract. Next, we utilized the Anselin's Local Moran's I statistic to identify statistically significant hot/cold spots of SNAP EBNE tracts throughout Texas and in Harris County. We found that hot spot census tracts had significantly higher densities, income levels, and lower poverty rates than other census tracts. Using spatial statistics to identify hot/cold spots of SNAP under-participation offers a novel method for understanding area SNAP utilization.